Institutionalizing a Culture of Student Mentoring within a Whole-School Approach: An Integrative Literature Review with a Systematic Search - Putra Asga Elevri; Yadi Ruyadi; Encep Syarief Nurdin; Asep Dahliyana; Juntika; Momod Abdul Samad (Lembaga Bale Literasi, 2026)
Schools are increasingly required to focus not only on academic achievement but also on supporting student development, character building, and psychological well-being. In this context, student mentoring needs to be understood as both a relational and institutional practice that takes place within the school ecosystem. This article aims to synthesize the literature on the institutionalization of a student mentoring culture within a holistic school approach, by examining relational mechanisms, school conditions, and implementation factors that support the sustainability of mentoring practices. This study employs an integrative literature review approach using systematic searches and thematic synthesis. The literature is analyzed through three dimensions. First, relational mechanisms include teacher–student relationships, mentoring, school connectedness, school belonging, and student engagement. Second, school conditions include school climate, school culture, character education, student well-being, and the whole-school approach. Third, institutional factors include implementation quality, sustainability, leadership, ownership, the balance between fidelity and adaptation, and organizational routines. The synthesis indicates that student mentoring is best understood as a relational, ecological, and institutional process that has the potential to support character and psychological well-being when supported by adequate school conditions and implementation. This article is not an evaluation of the effectiveness of a specific program, but rather a literature synthesis that examines the contextual relevance of Indonesian policies.